2020
DOI: 10.3390/jcm9072205
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Digital Workflows for Refractive Error Measurements

Abstract: Advancements in clinical measurement of refractive errors should lead to faster and more reliable measurements of such errors. The study investigated different aspects of advancements and the agreement of the spherocylindrical prescriptions obtained with an objective method of measurement (“Aberrometry” (AR)) and two methods of subjective refinements (“Wavefront Refraction” (WR) and “Standard Refraction” (StdR)). One hundred adults aged 20–78 years participated in the course of the study. Bland–Altman analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, Lin et al [25] found narrower agreement limits between VX120 and Topcon KR-800 for these components. The absolute differences within ±0.50 D were lower for J 0 (81.52%) and J 45 (82.62%), which many studies said was the acceptable error range for the minimum refractive results [12][13][14] . This pattern underscores their unreliability as effective measures for assessing astigmatism.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, Lin et al [25] found narrower agreement limits between VX120 and Topcon KR-800 for these components. The absolute differences within ±0.50 D were lower for J 0 (81.52%) and J 45 (82.62%), which many studies said was the acceptable error range for the minimum refractive results [12][13][14] . This pattern underscores their unreliability as effective measures for assessing astigmatism.…”
Section: Discussionmentioning
confidence: 79%
“…Refractive errors [spherical diopters (DS), cylinder diopters (DC), axis (A)] were measured three times in each eye. If any two measurements of one instrument differed by more than 0.50 D, another set of three consecutive measurements was required until the difference between any two measurements within a group was less than 0.50 D. Currently, many studies suggest ±0.50 D as the acceptable error range for clinically reliable refractive measurements to avoid poor measurements caused by overaccommodation or underaccommodation in the measurement process of children [12][13][14] . Parameters and Definitions We used power vectors (Thibos et al [11] ) to express clinical measurements: SE=DS+DC/2; J 0 =-DC/2×cos(2A); J 45 =-DC/2×sin(2A), where DS is sphere, DC is cylinder and A is axis.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…We have tools and screening methods that utilize machine learning techniques [29][30][31] in order to determine whether or not corneal refractive surgery is appropriate for the patient. Through the use of digital workflows, we are also able to obtain more accurate and reliable measurements of refractive errors [32]. Our recommendation also includes the utilization of a single digital file for each individual patient, with the objective of minimizing the number of transcription errors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers142 143 use power vectors and second derivatives of dioptric power curves143 to study variation of power and thus imaging over the retina as induced by fractal contact lenses (basically a multizone bifocal design) and these lenses and similar spectacle144 lenses are likely to be important in reducing the progression of myopia in younger eyes that is an increasing problem possibly relating to insufficient time spent outdoors145 and too much activity with tablets, mobile phones and other online media often with small screens, sometimes held at close distances for lengthy periods. New methods for objective and/or subjective ophthalmic refraction120 124 146–148 with some based on remote measurement of refraction via the internet148 and their analysis and understanding also use vectors124 147–153 or matrices64 68–70 for dioptric power and astigmatism 149 150. Given the need to address the ever-increasing prevalence of myopia and its associations61–63 131 132 154 and potential risks to ocular and retinal health relating indirectly to changes in axial length147 over time and the consequent economic and social cost implications of myopic-related disorders such as maculopathy and retinal detachment, methodology to better understand and analyse data of this type and its management91 131–136 143–145 155 are important in preventing unnecessary vision impairment and human affliction and suffering.…”
Section: Discussionmentioning
confidence: 99%